2002
DOI: 10.2166/wst.2002.0553
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale testing membrane bioreactor for wastewater reclamation in industrial laundry

Abstract: A pilot-scale study of membrane bioreactor treatment for reclamation of wastewater from Berendsen Textile Service industrial laundry in Søborg, Denmark was carried out over a 4 month period. A satisfactory COD degradation was performed resulting in a low COD in the permeate (< 50 mg/l). To obtain satisfactory treatment, addition of nitrogen was necessary. The biodegradability of the permeate was very low (BOD5 < 2 mg/l). A hydraulic retention time of 1 d turned out to be sufficient at a sludge concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…Comparable results were found by Ref. [10], who obtained sludge yields between 0.14 and 0.16 g TSS/g COD degraded for an MBR fed with laundry wastewater. In contrast to these observations [7] report an unexpectedly high sludge yield of 0.29 at a F/M ratio of 0.1 g COD/gTSS.…”
Section: Surplus Sludge Productionsupporting
confidence: 67%
“…Comparable results were found by Ref. [10], who obtained sludge yields between 0.14 and 0.16 g TSS/g COD degraded for an MBR fed with laundry wastewater. In contrast to these observations [7] report an unexpectedly high sludge yield of 0.29 at a F/M ratio of 0.1 g COD/gTSS.…”
Section: Surplus Sludge Productionsupporting
confidence: 67%
“…Similarly, after the same duration of air interruption, the recovery times were 4, 4, 24, 28 and 24 h respectively. The longest recovery times were observed after interruption of both air and feed simultaneously (40,40,4,24,48 h respectively). None of the parameters recovered to preinterruption levels within 48 h of a 25-day feed interruption.…”
Section: Biological Treatment Systemsmentioning
confidence: 97%
“…During the same period, simple physical separators coupled with disinfection processes were being developed and installed in individual houses. 19,22,23 In the late 1990s, reports also emerged on the use of advanced technologies such as membrane bio-reactors (MBRs) [24][25][26][27] and cheaper extensive technologies such as reed beds [28][29][30][31] and ponds. 32,33 Interestingly, only three chemical treatments-electro-coagulation, 34 Schemes for greywater recycling are found in most parts of the world.…”
Section: Treatment Technologies For Greywater Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…); 30 mg/L (max. PO 4 -P, mg/L 15 AE 23 0.5 TP, mg/L 11* -E. coli, CFU/100 mL -4 Â 10 6 * Fecal, CFU/100 mL 4 Â 10 4 * 8 Â 10 5 AE 2 Â 10 5 Total coliform, CFU/100 mL 4 Â 10 7 AE 5 Â 10 7 1 Â10 4 AE 1 Â10 5 References (Surendran and Wheatley, 1998;Andersen et al, 2002;SostarTurk et al, 2005;Friedler, 2004;Friedler et al, 2006;Gilboa and Friedler, 2008) (Surendran and Wheatley, 1998;Friedler et al, 2006;Gilboa and Friedler, 2008;Nolde, 2000;Friedler et al, 2005;Lamine et al, 2012;Hourlier et al, 2010;Ronen et al, 2010;Pidou et al, 2008;Zhang et al, 2009) Note: * indicates only one cited literature source reported the data. that the use of siliceous soil in SP-VFWs and SB-VFWs has met with limitations due to relatively low hydraulic conductivity and its tendency to clog (Platzer and Mauch, 1997;Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%